Simplified expressions for calculating Debye temperature and melting point of II-VI and III-V semiconductors - Daoud, Salah (International Journal of Scientific World, 2015)
Simple empirical expressions between the Debye temperature and the bond length and also between the melting point and the bond length have been proposed. These formulas have been established for two groups of ANB8-N type binary semiconductors (groups: II-VI and III-V). A good correlation between the Debye temperature and the bond length and also between the melting point and the bond length is obtained. The minimum average percentage deviations in the present approach reveal that our model proves its identity and soundness compared to those of other author relations.